2018
DOI: 10.3892/mmr.2018.9247
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of miR‑486‑5p in papillary thyroid carcinoma tissue: A study based on microarray and miRNA sequencing

Abstract: Abnormal expression of microRNA (miR) is associated with the occurrence and progression of various types of cancers, including papillary thyroid carcinoma (PTC). In the present study, the aim was to explore miR-486-5p expression and its role in PTC, as well as to investigate the biological function of its potential target genes. The expression levels of miR-486-5p and its clinicopathological significance were examined in 507 PTC and 59 normal thyroid samples via The Cancer Genome Atlas (TCGA). Subsequently, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…It is already known that miR-146b, miR-21, miR-221, miR-222, miR-181b are dysregulated in PTC. These molecules showed potential as biomarkers in PTC tissue and plasma/serum studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. It was also demonstrated that downregulation of miR-181b inhibits proliferation and promotes apoptosis in thyroid cancer TPC1 cells, making this miRNA a possible target for PTC treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is already known that miR-146b, miR-21, miR-221, miR-222, miR-181b are dysregulated in PTC. These molecules showed potential as biomarkers in PTC tissue and plasma/serum studies [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. It was also demonstrated that downregulation of miR-181b inhibits proliferation and promotes apoptosis in thyroid cancer TPC1 cells, making this miRNA a possible target for PTC treatment [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with low miR-486-5p showed a shorter overall survival as compared patients with high miR-486-5p level. These data suggest that miR-486-5p is implicated in thyroid cancer initiation and progression [142]. FBN1 was identified as a direct target of miR-486-5p in PTC cells [143].…”
Section: Micrornas In Differentiated Thyroid Cancermentioning
confidence: 80%
“…Dysregulation of miRNAs may lead to malignant transformation of cells, and they also participate in regulating the malignancy of cancer cells. 27 31 miR-543 has been reported to be crucial regulator in tumors. For example, miR-543 enhances the migration, invasion, and EMT of esophageal cancer cells via targeting phospholipase A2 group IVA; 32 miR-543 is overexpressed in colorectal cancer tissues and cell lines, and high expression of miR-543 is associated with shorter overall survival time and disease-free survival time of the patients, and it promotes the proliferation and metastasis of cancer cells by targeting KLF4 .…”
Section: Discussionmentioning
confidence: 99%